Sulfide-binding hemoglobins: Effects of mutations on active-site flexibility - Fernandez-Alberti, S. (2006)
The dynamics of Hemoglobin I (HbI) from the clam Lucina pectinata, from wild-type sperm whale (SW) myoglobin, and from the L29F/H64Q/V68F triple mutant of SW, both unligated and bound to hydrogen sulfide (H2S), have been studied in molecular dynamics simulations. Features that account for differences in H2S affinity among the three have been examined. Our results verify the existence of an unusual heme rocking motion in unligated HbI that can promote the entrance of large ligands such as H2S. The FQF-mutant partially reproduces the amplitude and relative orientation of the motion of HbI's heme group. Therefore, besides introducing favorable electrostatic interactions with H2S, the three mutations in the distal pocket change the dynamic properties of the heme group. The active-site residues Gln-64(E7), Phe-43(CD1), and His-93(F8) are also shown to be more flexible in unligated HbI than in FQF-mutant and SW. Further contributions to H2S affinity come from differences in hydrogen bonding between the heme propionate groups and nearby amino acid residues.